1996
DOI: 10.1103/physrevb.53.9353
|View full text |Cite
|
Sign up to set email alerts
|

Far-infraredc-axis response ofLa1.87Sr

Abstract: Far-infrared c-axis response of (La, Sr)2CuO4-delta determined by ellipsometry Henn, R.; Kircher, J.; Cardona, M.; Wittlin, A.; Duijn, V.H.M.; Menovsky, A.A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
10
2
Order By: Relevance
“…2͒ we observe in total four phonon modes. We note that, contrary to our earlier reports, 10,19 for the Sr doped samples we do not observe a splitting of the strongest mode at 235 cm Ϫ1 . We attribute this difference to a lower quality of the crystal used in the previous work.…”
Section: A Assignment Of the Modescontrasting
confidence: 86%
See 1 more Smart Citation
“…2͒ we observe in total four phonon modes. We note that, contrary to our earlier reports, 10,19 for the Sr doped samples we do not observe a splitting of the strongest mode at 235 cm Ϫ1 . We attribute this difference to a lower quality of the crystal used in the previous work.…”
Section: A Assignment Of the Modescontrasting
confidence: 86%
“…1͒, it has been concluded that they arise from the Brillouin zone folding produced by the orthorhombic distortion of the crystal. 10,19 Consistent with the small orthorhombic distortion, both modes have a small oscillator strength. The two stronger modes at 235 cm Ϫ1 and 500 cm Ϫ1 are already present in the tetragonal high-temperature phase and represent two of the three expected c-polarized, infrared-active A 2u modes for the tetragonal phase ͑for the orthorhombic phase six infrared-active modes having c polarization, corre- sponding to B 1u symmetry, are predicted based on symmetry considerations͒.…”
Section: A Assignment Of the Modesmentioning
confidence: 60%
“…[8][9][10][11][12] It is found that only in the superconducting state does there develop a plasma edgelike structure out of the otherwise insulatorlike normal state c-axis reflectivity.…”
mentioning
confidence: 99%
“…While there is no disagreement about the position of the peaks, 13 the interpretation of the continuum between them remains in dispute. Kim et al point 11 to signatures of incoherent transport above T c , i.e., a Drude liquid with an extremely high scattering rate and plasma frequency ͑''dirty'' limit parametrization.͒ However, Tamasaku et al, 2 and later Henn et al, 12 interpret very similar data using a Drude model with a small scattering rate and plasma frequency ͑pa-rametrization approaching the ''clean'' limit.͒ Below T c the optical response is dominated by the plasma edge. The c-axis absorptivity in 214 materials is much larger than the in-plane absorptivity, and hence the plasma edge dominated the loss seen in the early investigations using the polycrystalline samples.…”
Section: Introductionmentioning
confidence: 96%
“…[5][6][7][8][9] More recently, single crystals have become available, and the c-axis optical response has been measured separately from the in-plane optical response. 2,10,11,12 Above T c , the far-infrared reflectivity along the c axis is typical of a doped insulator, with strong phonon peaks seen on top of an electronic background. While there is no disagreement about the position of the peaks, 13 the interpretation of the continuum between them remains in dispute.…”
Section: Introductionmentioning
confidence: 98%